Does metoclopramide impair anastomotic healing of the left colon of rats? - Silva,Silvana Marques e (2011)
PURPOSE: To evaluate the effects of metoclopramide on the formation of adhesion and the healing of left colonic anastomoses in rats. METHODS: Forty rats underwent sectioning of the left colon and end-to-end anastomosis and were divided into two groups of 20 animals for the administration of metoclopramide (experimental group - E) or saline solution (control group - C). Each group was divided into subgroups of 10 animals each to be killed on the third (E3 and C3) or seventh postoperative day (E7 and C7). Adhesion was assessed, and a colonic segment containing the anastomosis was removed for analysis of breaking strength and hydroxyproline concentration. RESULTS: There were no deaths or dehiscence on the 3rd postoperative day. There was one death and one blocked anastomotic dehiscence in the E7 group. No significant differences between groups were found in the analysis of clinical outcome, intra-cavity adhesion, adhesion to the anastomosis or breaking strength on the 3rd and 7th postoperative day. Hydroxyproline concentration was higher in the control group on the 3rd (p=0.006) but not on the 7th postoperative day (p=0.241). CONCLUSION: Metoclopramide did not have harmful effects on the healing of intestinal anastomoses in rats.